Applying lean thinking in an educational institute – an action research. Issue 5 (12th June 2017) - Narayanamurthy, Gopalakrishnan; Gurumurthy, Anand; Chockalingam, Raju
Abstract : Purpose: Lean thinking (LT) has been implemented in various manufacturing and service sectors. But, only a few published research articles have developed a framework describing the procedure for implementing LT in an educational institute. The purpose of this paper is to develop and demonstrate a framework that can provide a structured procedure for the implementation of LT in an educational institute. Design/methodology/approach: Various LT tools and techniques applicable in educational institute were identified by reviewing the relevant literature. By adopting an action research methodology (ARM) for a time period of 28 months, the processes in a case institute were studied; wastes in the process were identified and various solutions were proposed and implemented. Findings: A comparison of the performance measures before (Batch 1) and after (Batch 2) implementation of solutions provided interesting insights into the effectiveness of LT. In both the batches, absenteeism in the class was found to increase across the terms. But the magnitude of increase was lesser in Batch 2. Results also showed that the number of unfilled seats (poor utilization) in an elective course in the second year of the program drastically reduced in Batch 2. Finally, a framework that can guide LT implementation in educational institutes was proposed. Research limitations/implications: The current study describes only the initial stages of implementation in an educational institute. Hence, some of the benefits discussed are expected in the long run which can be assessed by carrying out a longitudinal study. Future study can attempt to empirically validate the proposed framework in multiple educational institutes and theoretically explain the reasons behind the results obtained. Practical implications: ARM can be used as a tool by practitioners to study the behavioral aspects of employees of educational institutes toward LT implementation. The proposed framework and its demonstration can assist employees in educational institutes to implement LT. Positive results obtained in this study can further motivate the educational institutes to consider LT as a potential tool for improving the processes. Originality/value: This is the first study to develop and validate a framework for structured implementation of LT in the processes of an educational institute. The study is also unique in empirically capturing the impact of LT implementation of an educational institute by analyzing the archived data.